Concrete slump retaining agent and preparation method thereof
Through the synergistic effects of polycarboxylic acid water reducer, modified sodium lignin sulfonate, nanosilicate microcapsule sustained release agent, bio-based polyol and gardenia glycoside, the problems of insufficient slump retaining, poor cement adaptability and environmental protection in high temperature environments are solved, and efficient and stable concrete fluidity and strength improvement are achieved.
Patent Information
- Application Number
- CN202510403608.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-07-11
AI Technical Summary
The existing slump retaining agent has a short slump retaining time under high temperature environments, insufficient adaptability to different cements, a great impact on strength, and poor environmental protection in preparation, making it difficult to meet the long-term slump protection needs of modern projects.
The synergistic effect of polycarboxylic acid water reducer, modified sodium lignin sulfonate, nanosilicate microcapsule sustained release agent, bio-based polyol and plant extract gardeniasin is used to form a concrete slump retainer in combination with the optimized preparation process.
It significantly extends the concrete fluidity retention time, improves the adaptability to different cements, promotes stable development of strength, and achieves green and environmentally friendly production, which is suitable for high-temperature and long-distance construction.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and specifically to a concrete slump retaining agent and a preparation method thereof. Background Art
[0002] As the most commonly used structural material in construction engineering, the fluidity of the concrete mixture (usually expressed by slump) directly affects the construction performance and engineering quality. In practical applications, especially in high-temperature environments, long-distance transportation, or long-term storage, the concrete mixture is prone to slump loss due to the accelerated cement hydration reaction, resulting in a decrease in fluidity and affecting the pumping performance and pouring quality. To solve this problem, slump retaining agents, as an important type of concrete admixture, have been widely studied and applied. Their main function is to extend the fluidity retention time of the concrete mixture by regulating the cement hydration process or improving particle dispersion.
[0003] Currently, common slump retaining agents on the market are mostly based on polycarboxylate water reducers, supplemented with slow-release components or regulators. However, they have poor adaptability to different brands of cement and are prone to causing a decrease in the early strength of concrete by about 5%-10%. These existing technologies indicate that traditional slump retaining agents have the following deficiencies:
[0004] Limited slump retaining performance: Under high-temperature or long-term conditions, the slump retention time usually does not exceed 2 hours, making it difficult to meet the requirements of modern projects for long-term slump retention (such as long-distance pumping of super high-rise buildings).
[0005] Insufficient cement adaptability: Due to differences in cement composition (such as C3A content, mineral admixture ratio), some slump retaining agents show unstable performance and even cause bleeding or segregation phenomena.
[0006] Strength influence problem: Excessive use of slow-release components (such as gluconates) may delay excessive cement hydration, resulting in a decrease in the 7-day or 28-day compressive strength and affecting the structural safety.
[0007] Poor environmental friendliness: Volatile organic solvents (such as methanol, ethanol) are often used as reaction media in traditional preparation processes, or high-COD waste liquids are generated, increasing the risk of environmental pollution.
[0008] In recent years, some studies have attempted to improve the slump retention performance of slump-reducing agents by introducing slow-release microcapsules or bio-based materials. For example, the literature "Research Progress of Concrete Admixtures" (2020) reported a technology of coating inorganic slow-release agents with polyacrylate, which can extend the slump retention time to a certain extent. However, the microcapsule preparation process is complex, the cost is high, and the stability of the coating material is easily affected in acidic and alkaline environments. In addition, bio-based polyols (such as glycerol) are used in some admixtures due to their low toxicity and lubricity, but their individual use effect is limited and they need to act synergistically with other components. Plant extracts (such as geniposide) have been applied in the food and pharmaceutical fields as natural chelating agents, but the research in concrete admixtures is still blank, and their potential calcium ion chelating effect has not been fully explored.
[0009] In summary, there are still technical bottlenecks in the high-temperature long-term slump retention performance, broad-spectrum cement adaptability, strength retention, and green preparation process of existing slump-reducing agents. Therefore, it is of great significance to develop a concrete slump-reducing agent with high efficiency, strong adaptability, environmental protection, and simple preparation process. Summary of the Invention
[0010] The purpose of the present invention is to provide a concrete slump-reducing agent to solve the problems raised in the above background technology.
[0011] To achieve the above purpose, the present invention provides the following technical solutions:
[0012] A concrete slump-reducing agent is composed of the following components by mass percentage:
[0013] Polycarboxylate superplasticizer mother liquor, ether type, solid content 40%-42%, molecular weight 2000-3000, content 50%-60%;
[0014] Modified lignosulfonate, hydroxyl mass percentage 0.5%-1.0%, content 10%-15%;
[0015] Nanosilicate microcapsule slow-release agent, silicate radical slow-release time 2-4 hours, content 8%-12%;
[0016] Bio-based polyol, compounded by glycerol and xylitol in a mass ratio of 1:0.5-1:2, content 5%-10%;
[0017] Plant extract chelating agent, which is geniposide, content 2%-5%;
[0018] Deionized water, conductivity <10 μS / cm, the balance to 100%.
[0019] As a preferred technical solution of the present invention, the preparation method of the modified sodium lignosulfonate is as follows: In a stirring reaction kettle, industrial sodium lignosulfonate with a molecular weight of 1000 - 3000 is mixed with a hydrogen peroxide solution with a concentration of 3% - 5% at a mass ratio of 1:0.2, stirred and reacted at 50°C ± 2°C at 400 revolutions per minute for 2 hours, and after the reaction, dried at 70°C ± 5°C and a vacuum degree of 0.09 MPa for 5 hours to obtain the modified sodium lignosulfonate, with a yield ≥ 95%.
[0020] As a preferred technical solution of the present invention, the preparation method of the nano-silicate microcapsule sustained-release agent is as follows: Using a sodium silicate solution with a concentration of 22% - 25% as the raw material, adding a microemulsion system of deionized water and an oil phase, the oil phase is a compound of cyclohexane and Span-80 at a mass ratio of 9:1, the mass ratio of the water phase to the oil phase is 1:3, stirred at 32°C ± 2°C and 900 revolutions per minute for 1 hour, the pH is adjusted to 9.0 ± 0.5, and a 5% polyacrylate solution is added dropwise for coating. After centrifugal separation, it is dried at 50°C for 6 hours to obtain nano-silicate microcapsules with a particle size of 50 - 100 nm.
[0021] As a preferred technical solution of the present invention, the glycerol purity in the bio-based polyol is ≥ 99%, the xylitol purity is ≥ 98%, stirred and mixed at 40°C ± 2°C at 250 revolutions per minute for 20 minutes, and the viscosity of the mixed solution is 50 - 80 mPa·s.
[0022] As a preferred technical solution of the present invention, the plant extract chelating agent geniposide is extracted from gardenia fruits by the water extraction method. After the extract is concentrated and purified, the purity is ≥ 95%, and the pH value of its 5% aqueous solution is 6.5 - 7.0.
[0023] As a preferred technical solution of the present invention, this slump retaining agent is used for C20 - C50 grade cement concrete, with a dosage of 0.15% - 0.25% of the mass of the cementitious material. Under the conditions of 35°C ± 2°C and a relative humidity of 60% - 70%, the initial slump is 220 mm ± 10 mm, the slump is ≥ 200 mm after 3 hours, and the 28-day compressive strength is increased by ≥ 5% compared with the concrete without the slump retaining agent.
[0024] The present invention also provides a preparation method of a concrete slump retaining agent, including the following steps:
[0025] (1) Prepare the modified sodium lignosulfonate: In a stirring reaction kettle, take 100 kg of industrial sodium lignosulfonate, add 20 kg of a hydrogen peroxide solution with a concentration of 3% - 5%, introduce nitrogen with a flow rate of 0.3 L / min, stir and react at 50°C ± 2°C at 400 revolutions per minute for 2 hours, and dry at 70°C and a vacuum degree of 0.09 MPa for 5 hours to obtain about 95 kg of the modified sodium lignosulfonate;
[0026] (2) Preparation of nano-silicate microcapsule sustained-release agent: Take 20 kg of sodium silicate solution with a concentration of 22%, add 10 kg of deionized water and 30 kg of oil phase. The mass ratio of cyclohexane to Span-80 is 9:1. Stir at 32 °C and 900 revolutions per minute for 1 hour, adjust the pH to 9.0, dropwise add 5 kg of polyacrylate solution with a concentration of 5% for coating, after centrifugal separation, dry at 50 °C for 6 hours to obtain about 18 kg of nano-silicate microcapsules;
[0027] (3) Compound slump retainer: In a stirring reaction kettle, take 50 kg of deionized water, add 55 kg of polycarboxylate superplasticizer mother liquor, heat up to 40 °C ± 2 °C, stir at 300 revolutions per minute for 10 minutes, successively add 12 kg of modified lignosulfonate, 10 kg of nano-silicate microcapsule sustained-release agent and 8 kg of bio-based polyol, stir for 20 minutes until homogeneous, dropwise add 3 kg of geniposide at a rate of 0.8 kg / min, continue to stir for 30 minutes, and cool to 25 °C ± 2 °C at a rate of 0.5 °C / min to obtain the finished product.
[0028] As a preferred technical solution of the present invention, in step (1), the addition rate of hydrogen peroxide solution is 0.5 kg / min, and the volume of the reaction kettle is 200 - 300 L.
[0029] As a preferred technical solution of the present invention, in step (2), the dropping rate of the polyacrylate solution is 0.15 kg / min, the centrifugal separation speed is 5500 revolutions per minute, and the drying humidity is controlled at 25% ± 5%.
[0030] As a preferred technical solution of the present invention, in step (3), the stirring reaction kettle operates under normal pressure, and the stirring speed during cooling is 100 revolutions per minute.
[0031] Compared with the prior art, the beneficial effects of the present invention are:
[0032] 1. The concrete slump retainer provided by the present invention significantly improves the slump retention performance of the concrete mixture through the synergistic effect of polycarboxylate superplasticizer, modified lignosulfonate, nano-silicate microcapsule sustained-release agent, bio-based polyol and geniposide. Especially in a high-temperature environment, this slump retainer can effectively extend the fluidity retention time of the concrete, which is better than that of traditional slump retainers. At the same time, it has good adaptability to cements of different strength grades and brands, avoids bleeding or segregation problems, and can promote the stable development of later strength, providing reliable support for high-temperature long-distance construction.
[0033] 2. The preparation method of the present invention optimizes process parameters to ensure the stability and production efficiency of the product. By using bio-based polyols to replace traditional organic solvents and combining with the natural chelating properties of the plant extract geniposide, the emissions of volatile organic compounds and environmental pollution are significantly reduced, achieving green and environmentally friendly production. In addition, the preparation process does not require complex high-pressure equipment, has a simple process, controllable costs, and is convenient for industrial promotion, providing a new efficient and environmentally friendly option for the field of concrete admixtures. Detailed implementation manners
[0034] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0035] The present invention provides a concrete slump retention agent and its preparation method, aiming to solve the problems of short slump retention time of existing slump retention agents in high-temperature environments, insufficient adaptability to different cements, and poor environmental friendliness during the preparation process. The following further elaborates on the technical content and implementation process of the present invention through specific examples, comparative examples, and detailed test data.
[0036] Example 1: Preparation of a concrete slump retention agent;
[0037] Formulation composition: To prepare 100 kg of concrete slump retention agent, the specific components and masses are as follows:
[0038] Polycarboxylate superplasticizer mother liquor: 55 kg (mass percentage 55%), an ether-type polycarboxylate superplasticizer is selected, with a solid content of 40.5% (by mass), a molecular weight of 2500 (determined by gel permeation chromatography), and a pH value of 6.5;
[0039] Modified sodium lignosulfonate: 12 kg (mass percentage 12%), the mass percentage of hydroxyl groups is 0.8% (determined by infrared spectroscopy, characteristic peak at 3400 cm -1 );
[0040] Nano-silicate microcapsule sustained-release agent: 10 kg (mass percentage 10%), the sustained-release time of silicate radicals is 3 hours (determined by the release test in water at 37°C);
[0041] Bio-based polyol: 8 kg (mass percentage 8%), composed of glycerol (purity 99.5%, density 1.26 g / cm 3 ) and xylitol (purity 98.5%, crystalline) compounded in a mass ratio of 1:1;
[0042] Plant extract chelating agent: 3 kg (mass percentage 3%), geniposide is selected, with a purity of 95% (determined by high performance liquid chromatography).
[0043] Deionized water: 12 kg (mass percentage 12%), with a conductivity of 5 μS / cm (measured at 25°C), prepared by reverse osmosis purification.
[0044] Preparation method: Preparation of modified lignosulfonate: Equipment: 200L stainless steel stirring reactor, equipped with an electric stirrer (power 2.2 kW), a heating jacket and a vacuum drying system.
[0045] Raw materials: 100 kg of industrial lignosulfonate (molecular weight 1500 - 2000, water content 5%, supplied by a certain paper company in Shandong), 20 kg of hydrogen peroxide solution (concentration 4% by mass, prepared by diluting 30% industrial grade hydrogen peroxide).
[0046] Operation: Put the lignosulfonate into the reactor, start the stirrer at 400 revolutions per minute, slowly add the hydrogen peroxide solution (control the addition rate at 0.5 kg / min through a peristaltic pump, with a total addition time of 40 minutes), and at the same time introduce nitrogen (flow rate 0.3 L / min, purity 99.9%) to prevent side oxidation reactions. Heat the jacket to 50°C (temperature control accuracy ±2°C), and react for 2 hours.
[0047] Post-treatment: After the reaction, transfer the product to a vacuum drying oven (model DZF - 6050), dry it at 70°C and a vacuum degree of 0.09 MPa for 5 hours, take samples every hour to detect the moisture content until the moisture < 1%, and obtain 95.2 kg of modified lignosulfonate, with a yield of 95.2%.
[0048] Preparation of nano-silicate microcapsule sustained release agent: Equipment: 100L emulsification reactor, equipped with a high-speed stirrer (power 1.5 kW) and a centrifuge (model LXJ - 400).
[0049] Raw materials: 20 kg of sodium silicate solution (concentration 22% by mass, industrial grade), 10 kg of deionized water, 30 kg of oil phase (28 kg of cyclohexane, 2 kg of Span - 80, mass ratio 9:1, and the hydrophilic-lipophilic balance value of Span - 80 is 4.3).
[0050] Operation: Add sodium silicate solution and deionized water into the reaction kettle, stir until homogeneous (300 revolutions per minute), slowly add the oil phase (adding time 15 minutes), heat up to 32 °C (temperature control accuracy ±2 °C), adjust the stirring speed to 900 revolutions per minute, and stir for 1 hour. Adjust the pH to 9.0 with 10% sodium hydroxide solution (about 0.5 kg) (measured with a precision pH meter). Subsequently, dropwise add 5 kg of polyacrylate solution (concentration 5%, molecular weight 5000, dropping speed 0.15 kg / min, total time 33 minutes), and continue to stir for 30 minutes.
[0051] Post-treatment: Transfer the reaction product to a centrifuge, centrifuge at 5500 revolutions per minute for 10 minutes to separate the solid, dry it in an oven at 50 °C and relative humidity of 25% for 6 hours, turning it over every 2 hours, to obtain 18.1 kg of nano-silicate microcapsules with a particle size of about 80 nm (measured by dynamic light scattering method, instrument model Malvern Zetasizer Nano ZS).
[0052] Preparation of compound slump retention agent: Equipment: 300L stainless steel stirring reaction kettle, equipped with a variable-frequency stirrer (power 3.0 kW), jacket heating and cooling system.
[0053] Operation: Add 12 kg of deionized water into the reaction kettle, start the stirrer to 300 revolutions per minute, add 55 kg of polycarboxylate superplasticizer mother liquor, heat it to 40 °C through the jacket (temperature control accuracy ±2 °C), and stir for 10 minutes until the solution is clear. Add 12 kg of modified lignosulfonate sodium (added in 3 times, 4 kg each time, with an interval of 2 minutes), 10 kg of nano-silicate microcapsules (added in 2 times, 5 kg each time, with an interval of 3 minutes), and 8 kg of bio-based polyol (4 kg of glycerol and 4 kg of xylitol, pre-mixed at 40 °C at 250 revolutions per minute for 20 minutes, viscosity 65 mPa·s, measured by a rotational viscometer) in sequence, and stir for 20 minutes until the system is homogeneous without agglomeration. Dropwise add 3 kg of geniposide (added through a dropping funnel, total time 3.75 minutes) at a speed of 0.8 kg / min, and continue to stir for 30 minutes.
[0054] Cooling: Pass cooling water through the jacket, cool down to 25 °C at a rate of 0.5 °C / min (total time about 30 minutes), reduce the stirring speed to 100 revolutions per minute, detect that the pH value of the finished product is 6.8 and the viscosity is 120 mPa·s, to obtain 100 kg of finished slump retention agent.
[0055] Example 2: Concrete slump retention agent with adjusted formula;
[0056] Formula composition:
[0057] Polycarboxylate superplasticizer mother liquor: 50 kg (50%);
[0058] Modified sodium lignosulfonate: 15 kg (15%);
[0059] Nanosilicate microcapsule sustained-release agent: 12 kg (12%);
[0060] Bio-based polyol (mass ratio of glycerol to xylitol is 1:2, 2.67 kg glycerol + 5.33 kg xylitol): 8 kg (8%);
[0061] Gardenoside: 2 kg (2%);
[0062] Deionized water: 13 kg (13%).
[0063] Preparation method: The same as Example 1, only adjusting the raw material ratio and dosage, and the specific operation details are the same. The pH value of the finished product is 6.7, and the viscosity is 115 mPa·s.
[0064] Comparative Example 1: Traditional slump-retaining agent;
[0065] Formulation composition:
[0066] Commercially available polycarboxylate superplasticizer mother liquor (solid content 40%, molecular weight 3000): 90 kg;
[0067] Sodium gluconate (industrial grade, purity 98%): 10 kg.
[0068] Preparation method: Add the polycarboxylate superplasticizer mother liquor and sodium gluconate to the stirring tank, stir at 500 revolutions per minute for 30 minutes until uniform, without subsequent modification or microcapsule preparation steps. The pH value of the finished product is 6.5, and the viscosity is 100 mPa·s.
[0069] Test example: Performance test
[0070] Test conditions: Concrete mix ratio: C30 grade, cement 350 kg / m 3 (P·O42.5, Huaxin Cement Factory), sand 750 kg / m 3 (medium sand, fineness modulus 2.8), gravel 1100 kg / m 3 (5 - 20 mm continuous grading), water 157.5 kg / m 3 (water-binder ratio 0.45).
[0071] Slump-retaining agent dosage: 0.2% (calculated based on the mass of the binder, 0.7 kg / m 3 )
[0072] Environmental conditions: Temperature 35°C ± 2°C, relative humidity 65% ± 5% (controlled by a thermostatic and humidistatic chamber).
[0073] Test method: Slump: According to GB / T50080-2016 "Standard Test Method for Properties of Ordinary Concrete Mixtures", test once per hour.
[0074] Compressive strength: Determined after 28-day curing in accordance with the Standard Test Method for Physical and Mechanical Properties of Concrete (GB / T 50081-2019).
[0075] Test results:
[0076] Table 1: Comparison of slump retention performance;
[0077]
[0078] Table 2: Comparison of compressive strength and setting time
[0079]
[0080] Table 3: Verification of process parameter optimization (based on Example 1)
[0081]
[0082] Data analysis: Slump retention performance;
[0083] In Examples 1 and 2, the slump loss rates within 3 hours were 8.9% and 9.1% respectively, far lower than 39.1% of Comparative Example 1 and 44.2% of the blank group, meeting the requirement of "slump ≥ 200 mm after 3 hours".
[0084] The nano-silicate microcapsule sustained-release agent delays cement hydration by slowly releasing silicate ions, and geniposide chelates calcium ions to further stabilize the system, synergistically enhancing the slump retention effect.
[0085] Compressive strength and setting time: The 28-day compressive strengths of Examples 1 and 2 were 38.5 MPa and 38.2 MPa respectively, showing a 6.9% and 6.1% increase compared to the blank group, meeting the requirement of "increase ≥ 5%". Comparative Example 1 only had an increase of 2.2%, indicating that the formulation of the present invention is more beneficial for the later strength.
[0086] The initial setting and final setting times were extended by about 40 - 70 minutes, which is suitable for high-temperature long-distance transportation construction.
[0087] Influence of process parameters: In Test Group 1 (too fast addition rate of hydrogen peroxide), the dispersibility of modified lignin decreased, resulting in slight delamination.
[0088] In Test Group 2 (too fast dropping rate of polyacrylate), the microcapsule coating was incomplete and the sustained-release effect was weakened.
[0089] In Test Group 3 (slightly faster cooling rate), the influence on performance was small, but a rate of 0.5 °C / min was still preferred.
[0090] Conclusion: The slump retaining agent of the present invention achieves the goal of maintaining a slump of ≥200 mm for 3 hours and increasing the 28-day compressive strength by ≥5% at 35°C through the scientific ratio of polycarboxylate superplasticizer mother liquor, modified lignosulfonate, nano-silicate microcapsule sustained-release agent, bio-based polyol, and geniposide, as well as the optimized preparation process. Compared with traditional slump retaining agents, the present invention has significant advantages in performance stability, environmental friendliness, and process controllability, and is suitable for industrial production and practical engineering applications.
[0091] The content not described in detail in this specification belongs to the prior art well-known to those skilled in the art. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A concrete slump retaining agent, characterized in that The concrete slump retention agent is composed of the following components by mass percentage: Polycarboxylate superplasticizer mother liquor, ether type, solid content 40%-42%, molecular weight 2000-3000, content 50%-60%; Modified sodium lignosulfonate, hydroxyl mass percentage 0.5%-1.0%, content 10%-15%; Nano-silicate microcapsule sustained-release agent, silicate radical sustained-release time 2-4 hours, content 8%-12%; Bio-based polyol, compounded by glycerol and xylitol according to a mass ratio of 1:0.5-1:2, content 5%-10%; Plant extract chelating agent, which is geniposide, content 2%-5%; Deionized water, conductivity <10 μS / cm, the balance is up to 100%.
2. The concrete slump retention agent according to claim 1, wherein The preparation method of the modified sodium lignosulfonate is as follows: In a stirring reaction kettle, industrial sodium lignosulfonate with a molecular weight of 1000-3000 is mixed with a 3%-5% hydrogen peroxide solution according to a mass ratio of 1:0.2, and stirred and reacted at 50°C ± 2°C at 400 revolutions per minute for 2 hours. After the reaction, it is dried at 70°C ± 5°C and a vacuum degree of 0.09 MPa for 5 hours to obtain modified sodium lignosulfonate, and the yield is ≥95%.
3. A concrete slump retention agent according to claim 1, characterized in that, The preparation method of the nano-silicate microcapsule sustained-release agent is as follows: Using a sodium silicate solution with a concentration of 22%-25% as the raw material, adding a microemulsion system of deionized water and oil phase, the oil phase is compounded by cyclohexane and Span-80 according to a mass ratio of 9:1, the mass ratio of the water phase to the oil phase is 1:3, stirred at 32°C ± 2°C and 900 revolutions per minute for 1 hour, the pH is adjusted to 9.0 ± 0.5, and a 5% polyacrylate solution is added dropwise for coating. After centrifugal separation, it is dried at 50°C for 6 hours to obtain nano-silicate microcapsules with a particle size of 50-100 nm.
4. A concrete slump retention agent according to claim 1, wherein In the bio-based polyol, the purity of glycerol is ≥99%, the purity of xylitol is ≥98%, and it is stirred and mixed at 40°C ± 2°C at 250 revolutions per minute for 20 minutes, and the viscosity of the mixed solution is 50-80 mPa·s.
5. A concrete slump retaining agent according to claim 1, characterized in that, The plant extract chelating agent geniposide is extracted from gardenia fruits by the water extraction method. After the extract is concentrated and purified, the purity is ≥95%, and the pH value of its 5% aqueous solution is 6.5-7.
0.
6. A concrete slump retaining agent according to any one of claims 1-5, characterized in that, This slump retention agent is used for C20-C50 grade cement concrete, and the dosage is 0.15%-0.25% of the mass of the cementitious material. Under the conditions of 35°C ± 2°C and relative humidity of 60%-70%, the initial slump is 220 mm ± 10 mm, the slump is ≥200 mm after 3 hours, and the 28-day compressive strength is increased by ≥5% compared with the concrete without the slump retention agent.
7. A preparation method of a slump retaining agent for concrete, which is used to prepare the slump retaining agent for concrete according to any one of claims 1-5, characterized in that, Including the following steps: (1) Preparation of modified sodium lignosulfonate: In a stirring reaction kettle, take 100 kg of industrial sodium lignosulfonate, add 20 kg of a 3%-5% hydrogen peroxide solution, introduce nitrogen, the flow rate is 0.3 L / min, stir and react at 50°C ± 2°C at 400 revolutions per minute for 2 hours, and dry at 70°C and a vacuum degree of 0.09 MPa for 5 hours to obtain about 95 kg of modified sodium lignosulfonate; (2) Preparation of nano-silicate microcapsule sustained-release agent: Take 20 kg of sodium silicate solution with a concentration of 22%, add 10 kg of deionized water and 30 kg of oil phase, the mass ratio of cyclohexane to Span-80 is 9:1, stir at 32 °C and 900 rpm for 1 hour, adjust the pH to 9.0, add 5 kg of polyacrylate solution with a concentration of 5% dropwise for coating, after centrifugal separation, dry at 50 °C for 6 hours to obtain about 18 kg of nano-silicate microcapsules; (3) Compound slump retention agent: In a stirring reaction kettle, take 50 kg of deionized water, add 55 kg of polycarboxylate superplasticizer mother liquor, heat up to 40 °C ± 2 °C, stir at 300 rpm for 10 minutes, add 12 kg of modified lignosulfonate, 10 kg of nano-silicate microcapsules and 8 kg of bio-based polyol in sequence, stir for 20 minutes until homogeneous, add 3 kg of geniposide dropwise at a speed of 0.8 kg / min, continue to stir for 30 minutes, and cool to 25 °C ± 2 °C at a rate of 0.5 °C / min to obtain the finished product.
8. The preparation method of a concrete slump retaining agent according to claim 7, characterized in that, In step (1), the feeding rate of hydrogen peroxide solution is 0.5 kg / min, and the volume of the reaction kettle is 200 - 300 L.
9. The preparation method of a concrete slump retaining agent according to claim 7, characterized in that, In step (2), the dropping rate of polyacrylate solution is 0.15 kg / min, the centrifugal separation speed is 5500 rpm, and the drying humidity is controlled at 25% ± 5%.
10. The preparation method of a concrete slump retaining agent according to claim 7, characterized in that, In step (3), the stirring reaction kettle operates under normal pressure, and the stirring speed during cooling is 100 rpm.